Co po postmodernizmie, czyli nostalgia za mocnym podmiotem. Na marginesie książki Ewy Domańskiej Historia egzystencjalna - GURCZYŃSKA-SADY, Katarzyna (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2013)
The article concerns the problem of the subject of historiography, raised by Ewa Domańska in her recently published book Historia egzystencjalna. Krytyczne studium narratywizmu i humanistyki zaangażowanej [„Existential History: Critical Approach to Narrativism and Emancipatory Humanities”] (PWN, Warsaw 2012). Domańska asks about the future of historiography at the time when the impact of the postmodern ideas ceases in the culture in general and provides a critical picture of the narrativist style in history. She focuses on the Anglo-American version of narrativism and attempts to point to the main trends that persisted among modern historians who were infl uenced by the narrativist approach. The present article is to be a ground for polemical questions concerning the «strong» subject postulated by Domańska, who constructs its fi gure in opposition to the «weak» subject, the alter-ego of postmodern subjectivity. The idea of the «new» subject has been criticized by indicating that the task of philosophy is to search for the subject rather than create it, even if the aims Domańska proposed to achieve may be actually valid.